A Bridge No More? Turkiye’s Geopolitical Significance in the Twenty-first Century - ÜNGÖR SUNAR, ÇAĞDAŞ (My University, 2024)
This article scrutinises popular convictions about Turkiye’s ‘bridge’ status between Asia and Europe in the twenty-first century. Unlike during the Cold War, when Turkiye enjoyed geopolitical leverage due to its proximity to Europe and the Soviet Union, today’s geopolitics is shaped by China’s rise and the shift of commercial nodes away from the Atlantic and towards the Pacific. This renders Turkiye a peripheral actor in Asia-to-Europe commodity flows, as well as in the ongoing rivalry between Washington and Beijing. Other factors adversely affecting Turkiye’s geopolitical significance include the decarbonisation process and the Fourth Industrial Revolution. The European Union’s declining demand for fossil fuels challenges Turkiye’s ambition to become an energy corridor between Central Asia and Europe. Likewise, Turkiye’s secondary role in the global supply chains for technology (semiconductors, cobalt, silicon) is undermining its bridge status.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Science, Technology and Society; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SOSYOLOJİ; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; SOCIOLOGY; POLITICAL SCIENCE; Sosyoloji ve Siyaset Bilimi; Sosyal Bilimler ve Beşeri Bilimler; Siyasi bilimler ve Uluslararası İlişkiler; Sociology and Political Science; Social Sciences & Humanities; Political Science and International Relations; Ankara; Asia-Pacific century; China; Fourth Industrial Revolution; India–Middle East–Europe Economic Corridor (IMEC); Indo-Pacific strategy; Middle Corridor; NATO; Russia; Turkish Straits; Turkiye; US–China rivalry